Emergence of breathers in non-linear pulse compression - Chowdury, Amdad (2022)
We report on the universality of the emergence of Akhmediev breathers in soliton effect pulse compression dynamics by using explicit analytic solutions of breathers and solitons in the non-linear Schrödinger equation. We show that at maximum compression point, a higher-order soliton and a breather solution are equivalent with a nearly identical full-width at half maximum duration. From this, we demonstrate numerically how breathers that develop in the initial stage of continuous wave supercontinuum generation transform into an ensemble of solitons in the presence of system perturbation.